Evaluating the effectiveness of the complementary therapy web application based on Kiddo game therapy on children with attention deficit hyperactivity disorder: a before and after study - Atefeh Arkani; Narges Norouzkhani; Azam Kheirdoust; Kosar Ghaddaripouri; Mohammad Reza Mazaheri Habibi (BMC Pediatrics)
Abstract Attention deficit hyperactivity disorder (ADHD) is one of the most common neurological disorders, especially in childhood. Children with ADHD may have symptoms such as an inability to maintain concentration and attention, inappropriate developmental performance, and impulsivity. Play therapy helps to improve such symptoms by making the treatment process attractive. Therefore, the purpose of this study was to investigate the effectiveness of the Kiddo game-based complementary therapy web application in this disorder. This study was conducted in 2022 on 40 children aged 4 to 12 years in 2 psychotherapy clinics located in two cities. The available sampling method was used to select participants. At first, the Conners questionnaire was completed by the children’s parents, and then the Kiddo web application was made available for two months. At the end, the Conners questionnaire was again completed by the parents. Nearly 31 children with ADHD were evaluated. The average age was 6.48 ± 1.89. The highest percentage of children was in preschool. A significant difference was observed between the average Conners scores before and after the intervention (P < 0.001). The results showed that complementary treatment based on play therapy improves the quality of life in ADHD children and reduce the amount and severity of the disorder. Intervention based on remote play therapy can be used as an effective, accessible, and low-cost intervention for children with ADHD.